THE ROLE OF PRICE INVOLVEMENT AND CONSUMER LOYALTY IN DRIVING REPEAT PURCHASE INTEREST : : Case Studi of d’SRUPUT UNSIKA - Muhamad Fauzi; Ajat Sudrajat (Institut Teknologi dan Bisnis Dewantara, 2024)
This study aims to analyze the relationship between price engagement, consumer loyalty, and repurchase intention at d'SRUPUT UNSIKA. This research uses a case study design to investigate complex phenomena in the context of d'SRUPUT UNSIKA. The target population consisted of 3,000 customers selected based on certain criteria such as frequency of visits or purchasing patterns. This method allowed for an in-depth exploration of the role of price engagement and consumer loyalty in driving repeat purchase interest. The study found a significant positive impact of price engagement on repurchase intention, while consumer loyalty had no significant positive effect. Recommendations include diversifying research variables beyond price engagement and loyalty, as well as considering factors such as product quality, taste, and promotion for a more comprehensive understanding.